Evaluasi Program Corporate Social Responsibility dan Community Development pada Industri Tambang dan Migas - Prayogo, Dody (UI Scholars Hub, 2011)
Corporate social responsibility (CSR) and community development (CD) programs are now a legal requirement that should be implemented by corporations after the enactment of UU No. 40 Tahun 2007 with the limited liability company. Especially for mining and oil corporations, CSR and CD programs are strategic and significant in order to develop good and reciprocal relationships between corporation and its stakeholders. The successes or failure of the implementation of CSR and CD will directly influence “social legitimacy” of the corporation. Hence, evaluation of the program implementation is strategic in order to assess the social performance of the corporations. The result of evaluation is also important to ensure the relationships between corporation and its social stakeholders. In this regard, this article deals with the meaning of evaluation (definition), how to conduct the evaluation (method), and what is the implication (significance) of CSR and CD program, socially, legally and commercially.